Politics of Environmental Policy, Co-Production, and Multi-Actor Governance in School-Based Systems - Adil Mubarak; Aldri Frinaldi; Nora Eka Putri; Boni Saputra (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Environmental governance issues in West Sumatra have impacted hydrometeorological disasters. The implementation of environmental policies has not been successful in managing the environment. This study analyzes the role of co-production in building knowledge-based governance in educational units. The focus of the study is directed at how the Environmental Care and Culture Movement in Schools (GPBLHS) can encourage the involvement of multiple actors, including schools, local governments, communities, and civil society organizations, in creating sustainable environmental knowledge. This study uses a qualitative approach with a case study design, located in four schools that have received the National Adiwiyata award: SDN 03 Pakan Labuah Bukittinggi, MTsN 10 Tanah Datar, SMPN 1 Payakumbuh, and SMAN 7 Padang. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using Grounded Theory techniques. The results show that the implementation of GPBLS in West Sumatra schools successfully integrates aspects of policy, curriculum, and school community participation. The co-production process takes place through active interactions between teachers, students, parents, local governments, and the community. The intensity of each actor's involvement varies. Schools act as both recipients of policies and producers of environmental knowledge, which is demonstrated through various innovations.